(3QSGdI aj GdcdGe Ydi GdHjJjf GdHOjYjfs
(3ChdgG (B:s
(3hHYO abO XaQJ HQSGdI dWQjaI hYLGdI XQjaI JOd Ydi aVd eDdagG hehVhY GdQSGdI GdcdGe Ydi GdHjJjf GdHOjYjf ai TCfjgeG GdHYjOjf s
(3BNQgG (B:s
(3hGdWhd gh GdeMH hgh EeG ZjQ UMjM Ch eQLhY ceG jXgQ HeQGLYI GdefGbTGJ GdJi bOefGgG hbO Bf fMHS YfGA Gdbde NTjI GdEWGdI GdehLHI ddedGdI hGddg SHMGfg hJYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdChbGa GdYGeI (B_ (3HZOGO (B(5622) s
Keywords: (3GdeLGejYs